2013
DOI: 10.1021/jp408214p
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interaction in the NH3–H2 and H2O–H2 Complexes by Molecular Beam Scattering Experiments: The Role of Charge Transfer

Abstract: New molecular beam scattering experiments are reported for the ammonia-hydrogen system recording with unprecedented resolution "glory" quantum interferences in the total cross sections. Direct comparison with the analogous water-hydrogen complex, investigated under the same experimental conditions, highlights relevant differences in the intermolecular interaction affecting the observables. Analysis of the electronic charge displacement accompanying formation of both complexes, calculated using very accurate ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
0
17
2
2
Order By: Relevance
“…In particular, state-to-state resolved DCSs for the inelastic scattering of ND3 with H2 at a collision energy of 580 cm −1 were measured by Tkáč et al (2015) and satisfactorily reproduced by quantal calculations. The isotropic part of the NH3-H2 PES was also probed by the molecular beam experiment of Pirani et al (2013), which has provided a further accuracy assessment by measuring the glory quantum interference structure. Finally, the rotational spectrum of the NH3-H2 van der Waals complex was measured very recently by Surin et al (2017) and the deduced rotational constants were found to agree within 1-2% with those predicted from the PES of Maret et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, state-to-state resolved DCSs for the inelastic scattering of ND3 with H2 at a collision energy of 580 cm −1 were measured by Tkáč et al (2015) and satisfactorily reproduced by quantal calculations. The isotropic part of the NH3-H2 PES was also probed by the molecular beam experiment of Pirani et al (2013), which has provided a further accuracy assessment by measuring the glory quantum interference structure. Finally, the rotational spectrum of the NH3-H2 van der Waals complex was measured very recently by Surin et al (2017) and the deduced rotational constants were found to agree within 1-2% with those predicted from the PES of Maret et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…The global minimum in the final potential deduced from an analytical fit to all data points has a depth D e of 267cm −1 and corresponds to a structure with intermolecular center-ofmass distance R=3.23 Å and H 2 collinear with the C 3v axis of ammonia at the nitrogen end (see Figure 1). This PES has been employed in studies of collision dynamics of NH 3 with H 2 (Maret et al 2009;Wiesenfeld et al 2011;Pirani et al 2013;Daniel et al 2014;Ma et al 2015;Tkáč et al 2015).…”
Section: Details On the Potential Surfacementioning
confidence: 99%
“…Recently, we showed that CT effects play a significant role in the bond stabilization of various types of gas-phase binary complexes involving hydrogenated molecules. 50,54,55 We therefore decided to modify the Ng-CCl 4 potential so to include a further conceivable stabilizing contribution arising from CT (V CT ). This term, assumed to depend on the overlap integral between external orbitals of the interacting partners and therefore expected to be stereo-selective, has been formulated as a sum of four (number of atom-bond interaction terms) exponentials which decrease with the distance r b (the distance from the Ng atom from the interaction center on each CX bond, b, of CX 4 ),…”
Section: Zero Order Finalmentioning
confidence: 99%
“…98,99 With frozen-geometry fragments and with additional constrain that Ng is allowed to move on the CCl 4 (CF 4 ) symmetry plane (isolated molecules present a T d symmetry), the geometry of Ng-CCl 4 (CF 4 ) is defined in terms of the distance R between the Ng and the C atom (located at the molecular CM) and the angle φ between the Ng-C axis and the C 3 symmetry axis of CCl 4 (CF 4 ). To study the presence of a CT component in these systems, we analyzed the electron density changes due to the interaction between CCl 4 (CF 4 ) and the Ngs by means of the charge displacement function (CDF), 100 which we have successfully used to study intermolecular weak interactions 48,50,[52][53][54][55]101,102 and chemical bonding in several diverse contexts. [103][104][105][106] …”
Section: A Computational Detailsmentioning
confidence: 99%